Feasibility of microsurgery in rural area as part of compulsory health service in Turkey: Replantation, free conventional, perforator, thin, and super thin flaps - Sakarya, Ahmet Hamdi (Acta Medica, 2023)
Objective: Region six in Turkey, an underdeveloped area with limited doctors, lacks experienced healthcare professionals, teamwork, assistants, and instruments, which limits the performance of complex procedures. It is generally discouraged to attempt complex microsurgery in these regions. This study aims to demonstrate the feasibility of microsurgery and provide guidance for ambitious young plastic reconstructive surgeons performing microsurgery in underdeveloped areas as part of a compulsory service program. Material and Methods: A retrospective analysis was conducted on patients who underwent free flaps, replantation, and revascularization surgeries performed by the author, the sole plastic surgeon in the rural area, between August 2018 and August 2020. The analysis included operation notes, outpatient clinic notes, as well as pre-operative and post-operative pictures. Results: A total of thirty-six microsurgical operations were performed on thirty-two patients. Two out of nineteen (10.5%) replantation attempts and one out of seventeen (5.8%) free flaps experienced failure. Among the flaps harvested, four were thin and four were super-thin. Furthermore, three out of five (60%) pediatric flaps encountered serious non-surgical complications, while most systemic complications were infection-related. All complications were effectively managed without the need for dispatch. Conclusion: Microsurgery can be safely performed during the compulsory work period in the region six. Tips such as open-loop anastomoses, staff training, and easy means of flap monitoring can facilitate microsurgery. However, it may be prudent to consider avoiding such procedures in pediatric patients due to potential non-surgical complications and challenges with the dispatch system.